Von "diutisk" zu "dynamisch", von "englisc" zu "anything-ish". "is(c)h" kontrastiv diachron - Luise Kempf; Matthias Eitelmann (Zeitschrift für Wortbildung)
German -isch and English -ish share a common Germanic origin, which is evidenced by striking similarities concerning the derivation of ethnic adjectives (englisch/English) or property-denoting adjectives (kindisch/childish). However, after an initial period of parallel characteristics, the two languages display drastic changes, with English developing an approximative sense when attached to adjectival bases (e.g. greenish) and expanding to a wide range of other word categories, while German -isch develops multiple functions and also comes to firmly occupy a morphological niche with non-native bases. The paper sheds light on the evolving divergence between German and English by presenting results from two diachronic corpus-based studies. Additionally, explanations with respect to the typological parameter of 'Boundary Permeability' are provided.